Free and Slave Labor in the Antebellum South: Perfect Substitutes or Different Inputs? - Field, Elizabeth B. (The Review of Economics and Statistics, 1988)
The substitutability between free and slave labor is examined, and the permissibility of aggregating the two in to a single labor variab le is investigated, using a translog production function. Slaves on large cotton farms worked in gangs; free labor was not observed to do so. Despite this, previous research has aggregated free and slave labor, and employed functional forms imposing strong restrictions on substitution. Estimation of the translog function shows that simple additive aggregation is not acceptable; on large farms, slaves and free labor were complements, while on small, nongang farms, they were substitutes. Copyright 1988 by MIT Press.